2007
DOI: 10.1063/1.2716763
|View full text |Cite
|
Sign up to set email alerts
|

A new application of the Korteweg–de Vries Benjamin-Ono equation in interfacial electrohydrodynamics

Abstract: We consider waves on a layer of finite depth governed by the Euler equations in the presence of gravity, surface tension, and vertical electric fields. We use perturbation theory to identify canonical scalings and to derive a Korteweg-de Vries Benjamin-Ono equation arising in interfacial electrohydrodynamics. When the Bond number is equal to 1 / 3, dispersion disappears and the equation reduces to the Benjamin-Ono equation. In the additional limit of vanishing electric fields, we show how to obtain a new evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 15 publications
0
56
0
3
Order By: Relevance
“…A normal electric field has been considered [3,4,5,6] when the field is due to parallel electrodes with separation distance comparable to the depth of the fluid. When the normal electric field tends to a constant far from the surface, corresponding to parallel electrodes with very large separation distance, a Kortweg-deVries Benjamin-Ono type equation is obtained for particular wavelength and amplitude scalings [7,8]. In the present paper a more general analysis for the normal electric field case derivation is provided, which allows for a wider range of wavelength and amplitude scalings and includes the effect of electrode separation distance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A normal electric field has been considered [3,4,5,6] when the field is due to parallel electrodes with separation distance comparable to the depth of the fluid. When the normal electric field tends to a constant far from the surface, corresponding to parallel electrodes with very large separation distance, a Kortweg-deVries Benjamin-Ono type equation is obtained for particular wavelength and amplitude scalings [7,8]. In the present paper a more general analysis for the normal electric field case derivation is provided, which allows for a wider range of wavelength and amplitude scalings and includes the effect of electrode separation distance.…”
Section: Introductionmentioning
confidence: 96%
“…We consider this case to allow direct comparison with earlier works [7,8]. However this case should correspond to the limit d → ∞, the exact nature of the limit emerges as part of the analysis presented in §3.…”
Section: Introductionmentioning
confidence: 99%
“…More than that, Barannyk et al showed in [15] that the tangential electric field can even suppress the RayleighTaylor instability in some situations. On the contrary, it can be deduced from the work by Gleeson et al [16], Papageorgiou et al [21], Lin et al [2], and Wang [8] that the normal electric field has a destabilizing effect on the interface. N. M. Zubarev and O. V. Zubareva [10,20] and Tao and Guo [22] considered the electrified gas-fluid or vacuumfluid interface so that they can make the assumption that the permittivity of the fluid was much larger compared to that of gas (the permittivities for pure water and air are 80 and 1, resp.).…”
Section: Introductionmentioning
confidence: 59%
“…The study of the stability of interfacial electrohydrodynamic waves was initiated by Melcher [3] and Taylor and McEwan [13], and the role of interfacial stresses resulting from electrodes was reviewed by Melcher and Taylor [4]. Recent theoretical research in this field has focused on the nonlinear phenomena and corresponding mechanisms, such as nonlinear coherent structures (e.g., [2,5,8,10,11,[14][15][16][17][18][19][20]) and touchdown singularities (e.g., [7,21]). Considerable effects have been put into the modeling and numerical studies of nonlinear interfacial electrohydrodynamic waves.…”
Section: Introductionmentioning
confidence: 99%
“…For E b = 0, it can be viewed as a forced Benjamin-Ono Korteweg de Vries equation. It generalises the unforced equation derived in [5].…”
Section: Weakly Nonlinear Theorymentioning
confidence: 99%